The Equilibrium and Optimal Timing of Price Changes - Ball, Laurence; Romer, David (Review of Economic Studies, 1989)
This paper studies the welfare properties of the equilibrium timing of price changes. Staggered price setting has the advantage that it permits rapid adjustment to firm-specific shocks, but the disadvantages that it causes unwanted fluctuations in relative prices and that, by creating price level inertia, it can increase aggregate fluctuations. Because each firm ignores its contribution to these problems, staggering can be a stable equilibrium even if it is highly inefficient. In addition, there can be multiple equilibria in the timing of prices changes; indeed, whenever there is an inefficient staggered equilibrium, there is also an efficient equilibrium with synchronized price setting.